2016
DOI: 10.1002/hon.2310
|View full text |Cite
|
Sign up to set email alerts
|

Risk and prognostic factors of transplantation‐associated thrombotic microangiopathy in allogeneic haematopoietic stem cell transplantation: a nested case control study

Abstract: Transplantation-associated thrombotic microangiopathy (TA-TMA) is a significant complication of haematopoietic stem cell transplantation. However, it remains controversial which clinical or laboratory markers are of evident risk and prognostic value. From 2006 to 2013, a nested case control study was carried out in our centre to study the risk and prognostic factors of TA-TMA. A total of 654 consecutive patients who underwent allogeneic haematopoietic stem cell transplantation were studied. Twenty-six (4.0%) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 20 publications
7
32
1
Order By: Relevance
“…Regarding predisposing factors, previous clinical studies have identified age, donor type, conditioning regimen, calcineurin inhibitors, GVHD, and infections as important risk factors for TA-TMA. 1,3,5,[8][9][10][11] In our study, the presence of GVHD was the only independent predictor for the development of TA-TMA, possibly related to systemic endothelial damage. Therefore, successful prevention and treatment strategies for GVHD need to be timely employed to prevent complications, as emphasized by Ye and colleagues.…”
supporting
confidence: 48%
See 3 more Smart Citations
“…Regarding predisposing factors, previous clinical studies have identified age, donor type, conditioning regimen, calcineurin inhibitors, GVHD, and infections as important risk factors for TA-TMA. 1,3,5,[8][9][10][11] In our study, the presence of GVHD was the only independent predictor for the development of TA-TMA, possibly related to systemic endothelial damage. Therefore, successful prevention and treatment strategies for GVHD need to be timely employed to prevent complications, as emphasized by Ye and colleagues.…”
supporting
confidence: 48%
“…Therefore, successful prevention and treatment strategies for GVHD need to be timely employed to prevent complications, as emphasized by Ye and colleagues. 1 CMV viremia found in the latter study as an independent factor is also closely related to GVHD, possibly consisting a confounding factor. Furthermore, experience from treatment outcomes in these lifethreatening complications may be useful for future treatment strategies.…”
supporting
confidence: 46%
See 2 more Smart Citations
“…23,24 On the other hand, II-IV aGVHD could be a risk factor for TA-TMA occurrence. [25][26][27][28][29] Immunosuppressors are typically used for GVHD prophylaxis and treatment; these agents can be important factors regarding the onset and deterioration of TA-TMA. 5,30 Unfortunately, some patients may develop both TMA and aGVHD after allo-HSCT, leading to considerable difficulties in diagnosis and treatment in these patients.…”
mentioning
confidence: 99%